Clinical and prognostic significance of detecting CEA, EGFR, LunX, c-met and EpCAM mRNA-positive cells in the peripheral blood, tumor-draining blood and bone marrow of non-small cell lung cancer patients - Rehulkova, Alona; Chudacek, Josef; Prokopova, Andrea; Vidlarova, Monika; Stranska, Jana; Drabek, Jiri; Potockova, Jana; Trojanec, Radek; Vrbková, Jana; Skarda, Josef; Bohanes, Tomas; Szkorupa, Marek; et al. (Translational lung cancer research, 2023)
BACKGROUND: Surgical treatment of early-stage non-small cell lung cancer (NSCLC) yields highest expectations for recovery. However, the frequency of further disease progression remains high since micro-metastatic disease may be undetected by conventional diagnostic methods. We test the presence and prognostic impact of circulating tumor cells (CTCs) in peripheral blood (PB), tumor-draining pulmonary blood (TDB) and bone marrow (BM) samples from NSCLC patients. METHODS: The presence of circulating/disseminated tumor cells (CTCs/DTCs) was detected by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) analysis in PB, TDB and BM samples before surgery in 119 stage IA-IIIA NSCLC patients (Clinical Trial NS10285). RESULTS: NSCLC patients with the presence of carcinoembryonic antigen (CEA) mRNA-positive CTCs/DTCs in TDB and BM had significantly shorter cancer-specific survival (CSS) (P<0.013, resp. P<0.038). Patients with the presence of epithelial cellular adhesion molecule (EpCAM) mRNA-positive CTCs in TDB samples had significantly shorter CSS and disease-free survival (DFS) (P<0.031, resp. P<0.045). A multivariate analysis identified the presence of CEA mRNA-positive CTCs in the PB as an independent negative prognostic factor for DFS (P<0.005). No significant correlation of CTCs/DTCs presence and other prognostic factors was found. CONCLUSIONS: In NSCLC patients undergoing radical surgery, the presence of CEA and EpCAM mRNA-positive CTCs/DTCs is associated with poorer survival.